Treatment Outcome Trends for Non-Ruptured Abdominal Aortic Aneurysms: A Nationwide Prospective Cohort Study. (February 2022) - Alberga, Anna J.; Karthaus, Eleonora G.; Wilschut, Janneke A.; de Bruin, Jorg L.; Akkersdijk, George P.; Geelkerken, Robert H.; Hamming, Jaap F.; Wever, Jan J.; Verhagen, Hence J.M.; ,; ,; van den Akker, P.J.; et al.
Abstract : Objective: The Dutch Surgical Aneurysm Audit (DSAA) initiative was established in 2013 to monitor and improve nationwide outcomes of aortic aneurysm surgery. The objective of this study was to examine whether outcomes of surgery for intact abdominal aortic aneurysms (iAAA) have improved over time. Methods: Patients who underwent primary repair of an iAAA by standard endovascular (EVAR) or open surgical repair (OSR) between 2014 and 2019 were selected from the DSAA for inclusion. The primary outcome was peri-operative mortality trend per year, stratified by OSR and EVAR. Secondary outcomes were trends per year in major complications, textbook outcome (TbO), and characteristics of treated patients. The trends per year were evaluated and reported in odds ratios per year. Results: In this study, 11 624 patients (74.8%) underwent EVAR and 3 908 patients (25.2%) underwent OSR. For EVAR, after adjustment for confounding factors, there was no improvement in peri-operative mortality (aOR [adjusted odds ratio] 1.06, 95% CI 0.94 – 1.20), while major complications decreased (2014: 10.1%, 2019: 7.0%; aOR 0.91, 95% CI 0.88 – 0.95) and the TbO rate increased (2014: 68.1%, 2019: 80.9%; aOR 1.13, 95% CI 1.10 – 1.16). For OSR, the peri-operative mortality decreased (2014: 6.1%, 2019: 4.6%; aOR 0.89, 95% CI 0.82 – 0.98), as well as major complications (2014: 28.6%, 2019: 23.3%; aOR 0.95, 95% CI 0.91 – 0.99). Furthermore, the proportion of TbO increased (2014: 49.1%, 2019: 58.3%; aOR 1.05, 95% CI 1.01 – 1.10). In both the EVAR and OSR group, the proportion of patients with cardiac comorbidity increased. Conclusion: Since the establishment of this nationwide quality improvement initiative (DSAA), all outcomes of iAAA repair following EVAR and OSR have improved, except for peri-operative mortality following EVAR which remained unchanged.